A exposição à fumaça de cigarro intensifica a remodelação ventricular após o infarto agudo do miocárdio - Zornoff, Leonardo Antonio Mamede [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Camapanha, Álvaro O. [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2006)
OBJETIVO: Analisar os efeitos da exposição à fumaça de cigarro (EFC) na remodelação ventricular após o infarto agudo do miocárdio (IAM). MÉTODOS: Ratos foram infartados e distribuídos em dois grupos: C (controle, n = 31) e F (EFC: 40 cigarros/dia, n = 22). Após seis meses, foi realizado ecocardiograma, estudo funcional com coração isolado e morfometria. Para comparação, foi utilizado o teste t (com média ± desvio padrão) ou teste de Mann-Whitney (com mediana e percentis 25 e 75). RESULTADOS: Os animais EFC apresentaram tendência a maiores áreas ventriculares diastólicas (C = 1,5 ± 0,4 mm², F = 1,9 ± 0,4 mm²; p = 0,08) e sistólicas (C = 1,05 ± 0,3 mm², F = 1,32 ± 0,4 mm²; p = 0,08) do VE. A função sistólica do VE, avaliada pela fração de variação de área, tendeu a ser menor nos animais EFC (C = 31,9 ± 9,3 %, F = 25,5 ± 7,6 %; p = 0,08). Os valores da - dp/dt dos animais EFC foram estatisticamente inferiores (C = 1474 ± 397 mmHg, F = 916 ± 261 mmHg; p = 0,02) aos animais-controle. Os animais EFC apresentaram maior peso do VD, ajustado ao peso corporal (C = 0,8 ± 0,3 mg/g, F = 1,3 ± 0,4 mg/g; p = 0,01), maior teor de água nos pulmões (C = 4,8 (4,3-4,8)%, F = 5,4 (5,1-5,5); p = 0,03) e maior área seccional do miócito do VE (C = 239,8 ± 5,8 µm², F = 253,9 ± 7,9 µm²; p = 0,01). CONCLUSÃO: A exposição à fumaça de cigarro intensifica a remodelação ventricular após IAM.

OBJECTIVE: To evaluate the role of cigarette smoke exposure (CSE) on ventricular remodeling following acute myocardial infarction (AMI). METHODS: Rats were submitted to myocardial infarction and divided into two groups: C (control, n = 31) and F (CSE: 40 cigarettes/day, n = 22). After 6 months, the survivors were submitted to echocardiogram, functional study with isolated heart, and morphometric analysis. For comparison purposes, we used the t test (mean ± standard deviation) or the Mann-Whitney test (with median and 25th and 75th percentiles). RESULTS: The CSE animals tended to have larger diastolic (C = 1.5 ± 0.4 mm², F = 1.9 ± 0.4 mm²; p = 0.08) and systolic (C = 1.05 ± 0.3 mm², F = 1.32 ± 0.4 mm²; p = 0.08) left ventricular(LV) areas. The systolic function of the LV, assessed according to the fractional area change, tended to be impaired in CSE animals (C = 31.9 ± 9.3%, F = 25.5 ± 7.6%; p = 0.08). The - dp/dt values for CSE animals were statistically lower (C = 1474 ± 397 mmHg, F = 916 ± 261 mmHg; p = 0.02) than for control animals. The CSE animals presented higher right ventricle (RV) weight adjusted for body weight (C = 0.8 ± 0.3 mg/g, F = 1.3 ± 0.4 mg/g; p = 0.01), higher content of water in lungs (C = 4.8 (4.3-4.8)%, F = 5.4 (5.1-5.5); p = 0.03), and larger LV myocyte cross-sectional areas (C = 239.8 ± 5.8 µm², F = 253.9 ± 7.9 µm²; p = 0.01). CONCLUSION: Cigarette smoke exposure intensifies ventricular remodeling following acute myocardial infarction.
Cigarette smoke exposure intensifies ventricular remodeling process following myocardial infarction
Keywords: Função ventricular; dilatação ventricular; hipertrofia ventricular; Ventricular function; ventricular dilatation; ventricular hypertrophy